2021
DOI: 10.3390/antiox10111786
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted “Green” Extraction (UAE) of Antioxidant Compounds (Betalains and Phenolics) from Opuntia stricta var. Dilenii’s Fruits: Optimization and Biological Activities

Abstract: Opuntia stricta var. Dillenii’s prickly pears are an underutilized fruit with a high content of betalains and phenolic compounds that could bring potential health benefits for humans. The aim of this study is the optimization of the “green” extraction of betalains and phenolic compounds from Opuntia stricta var. Dillenii’s whole fruits by ultrasound-assisted extraction (UAE), using a response surface methodology (RSM) by a central composite design (CCD) in order to obtain extracts rich in betalains and phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Additionally, it has been shown that betalains have the capacity to inhibit the enzymes lipoxygenase and cyclooxygenase-2 [51]. This finding was in accordance with the previous reports that shown betalains can also inhibit the hyaluronidase enzyme [60][61][62][63]. Another investigation showed that two of the compounds of our dye as betanidin (7%) and betanin (43%) were able to inhibit key enzymes related to gastric inflammation as COX by interaction with Tyr-385 and Ser-530 residues close to the active site of COX [64,65].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, it has been shown that betalains have the capacity to inhibit the enzymes lipoxygenase and cyclooxygenase-2 [51]. This finding was in accordance with the previous reports that shown betalains can also inhibit the hyaluronidase enzyme [60][61][62][63]. Another investigation showed that two of the compounds of our dye as betanidin (7%) and betanin (43%) were able to inhibit key enzymes related to gastric inflammation as COX by interaction with Tyr-385 and Ser-530 residues close to the active site of COX [64,65].…”
Section: Discussionsupporting
confidence: 91%
“…However, the UAE exhibited betacyanin (4.87 mg/g) and betaxanthin (2.64 mg/g) in red beets after 30 min extraction time at the solvent/sample ratio of 75 ml/g (Silva et al, 2020). Betalain content of 10.05 mg/g was obtained from Opuntia Dillenii whole fruit by ultrasonication treatment at 15% of ethanol and 20°C of temperature (Gómez‐López et al, 2021). The higher betacyanin content was found from ultrasound extraction (71.34 mg/100 g and 82.79 mg/100 g) as compared to Soxhlet extraction (17.64 mg/100 g and 18.67 mg/100 g) of peel and flesh of red dragon fruit, respectively (Ramli et al, 2014).…”
Section: Sources Of Plant Pigments and Benefits To Mankindmentioning
confidence: 99%
“…Consumption of β‐carotene, β‐cryptoxanthin, lutein, and zeaxanthin decreases the risk of developing prostate cancer by 15%. According to a meta‐analysis, the effects of carotenoids, lycopene, and β‐carotene are linked to a 30% reduction in the development of lung cancer (Gómez‐López et al, 2021). Among all, β‐carotene is the most ubiquitous and is present in abundance in several fruits and leafy vegetables.…”
Section: Sources Of Plant Pigments and Benefits To Mankindmentioning
confidence: 99%
“…Moreover, O. stricta extracts obtained from flowers and whole fruits or peels exhibited many pharmacological activities such as anti-spermatogenic, hypotensive, anti-oxidant, antibacterial, anti-inflammatory, antiviral, analgesic and anticancer [8][9][10][11][12][13][14][15][16]. These beneficial medicinal features are as a result of their chemical contents of antioxidants, pigments, and phenolic acids [17,18].…”
Section: Introductionmentioning
confidence: 99%